2018
DOI: 10.1186/s12887-018-1286-5
|View full text |Cite
|
Sign up to set email alerts
|

Gillespie syndrome in a South Asian child: a case report with confirmation of a heterozygous mutation of the ITPR1 gene and review of the clinical and molecular features

Abstract: BackgroundGillespie syndrome is a rare, congenital, neurological disorder characterized by the association of partial bilateral aniridia, non-progressive cerebellar ataxia and intellectual disability. Homozygous and heterozygous pathogenic variants of the ITPR1 gene encoding an inositol 1, 4, 5- triphosphate- responsive calcium channel have been identified in 13 patients recently. There have been 22 cases reported in the literature by 2016, mostly from the western hemisphere with none reported from Sri Lanka.C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…B , disease-associated mutations found in the regulatory and coupling domain ( 47 49 , 52 54 , 65 , 72 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 82 ). C, disease-associated mutations found in the C-terminal domain ( 52 53 , 54 55 , 65 , 83 84 , 85 , 86 , 87 , 88 89 ). Diseases associated with mutations in at least one isoform of IP 3 R include SCA29 ( blue ), Gillespie syndrome ( orange ), anhidrosis ( pink ), neuropathy ( green ), pontocerebellar hypoplasia ( dark blue ), spinocerebellar ataxia 15/16 ( light blue ), head and neck squamous cell carcinoma ( red ), Sézary Syndrome ( purple ), and familial isolated primary hyperparathyroidism ( gray ).…”
mentioning
confidence: 99%
“…B , disease-associated mutations found in the regulatory and coupling domain ( 47 49 , 52 54 , 65 , 72 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 82 ). C, disease-associated mutations found in the C-terminal domain ( 52 53 , 54 55 , 65 , 83 84 , 85 , 86 , 87 , 88 89 ). Diseases associated with mutations in at least one isoform of IP 3 R include SCA29 ( blue ), Gillespie syndrome ( orange ), anhidrosis ( pink ), neuropathy ( green ), pontocerebellar hypoplasia ( dark blue ), spinocerebellar ataxia 15/16 ( light blue ), head and neck squamous cell carcinoma ( red ), Sézary Syndrome ( purple ), and familial isolated primary hyperparathyroidism ( gray ).…”
mentioning
confidence: 99%
“…However, a small ZHp in the ITPR1 region from the current study indicated species specificity in plateau adaptive molecular mechanisms. Furthermore, recent reported heterozygous mutations and structural variants of ITPR1 genes are associated with the development of ataxia in the brains of human children (De Silva et al, ; Synofzik et al, ). As we know, plateau hypoxic environmental stimulation leads to an increase in the ratio of [HCO3‐]/[H2CO3] in the cerebrospinal fluid of animals, leading to the inhibition of central chemoreceptors, thus resulting in brain ataxia (Hainsworth, Drinkhil, & Rivera‐Chira, ).…”
Section: Resultsmentioning
confidence: 99%
“…So far, 25 genetically confirmed patients with Gillespie's syndrome have been reported. [10][11][12][13][14] In total, 12 mutations have been identified, including dominant and recessive variants. The mutations found in Gillespie's syndrome are, with one exception, localized either in the regulatory domain or in the C-terminal transmembrane domain of ITPR1 (►Fig.…”
Section: Discussionmentioning
confidence: 99%